98.6k views
5 votes
Type the correct answer in each box. Use numerals instead of words. If necessary, use / for the fraction bar(s).

Consider the given function.

pic below

Type the correct answer in each box. Use numerals instead of words. If necessary, use-example-1
User Chocksaway
by
5.1k points

1 Answer

4 votes

Answer:

  • To determine the inverse of the given function,

Change f(x) to y , switch x and y , and solve for y.

  • The resulting function may be written as:


f^(-1)x=(\ln (x+4))/(2)

Explanation:

We know that while finding the inverse of a function the following steps are to be followed:

  • We first put f(x)=y
  • Then we interchange x and y in the expression.
  • and then we finally solve for y.

We are given a function f(x) by:


f(x)=e^(2x)-4

Now, we put


f(x)=y

i.e.


e^(2x)-4=y

Now, we interchange x and y as follows:


e^(2y)-4=x

and finally we solve for y

i.e.


e^(2y)=x+4

Taking logarithmic function both the side of the equation we get:


2y=\ln (x+4)\\\\i.e.\\\\y=(\ln (x+4))/(2)

i.e.


f^(-1)x=(\ln (x+4))/(2)

User Axalix
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.